Effect of Calcium Supplementation During Pregnancy in Maternal Patient to Preterm Birth in One of Private Hospitals in Yogyakarta - Brilian, Albertus I.; Virginia, Dita Maria (Indonesian Journal of Clinical Pharmacy, 2017)
Calcium is one of micronutrients that plays an important role in pregnancy. Insufficient consumption of calcium in pregnant women could lead to preterm birth, which is a major cause of neonatal mortality. This study aimed to determine the maternal patientsâ characteristics, relationship between prematurity risk factors such as age, antenatal care, history of abortion and parity as well as calcium supplementation during pregnancy on pregnant women toward preterm birth in one of private hospitals in Yogyakarta. The survey was conducted from May to August 2016 The study was an analytical observation with crossâsectional research design. In total of 199 medical records of maternal patients that had been included were analyzed using Mann-Whitney and Chi-Square test to see the relationship of calcium supplementation to preterm birth. Fisherâs exact test was used if Chi-Squareâs requirement was not fulfilled. The pregnant womenâs characteristics in the hospital were expectant mothers with normal gestational age (93%); insufficient calcium supplementation (79%); age â¤30 years (61%); bachelorâs degree (53%); private employees (40%); antenatal care â¥4 (98%) and parity 1 and â¥4 (54%). The result of this study showed there was no relationship between age, antenatal care, history of abortion and parity as well as calcium supplementation toward preterm birth on pregnant women in one of private hospitals in Yogyakarta.Keywords: Calcium supplementation, maternal, preterm birthÂ Pengaruh Suplementasi Kalsium pada Pasien Maternal Selama Kehamilan terhadap Kelahiran Prematur di Salah Satu Rumah Sakit Swasta di YogyakartaKalsium merupakan salah satu mikronutrien yang memainkan peran penting pada masa kehamilan. Pengonsumsian kalsium yang kurang pada ibu hamil dapat menyebabkan kelahiran prematur (kelahiran <37 minggu) yakni penyebab utama kematian neonatal. Penelitian ini bertujuan untuk mengetahui karakteristik pasien maternal, hubungan faktor-faktor risiko seperti antenatal care, umur, riwayat abortus dan paritas serta suplementasi kalsium selama kehamilan terhadap kelahiran prematur di salah satu rumah sakit swasta di Yogyakarta. Penelitian ini dilakukan pada bulan Mei hingga Agustus 2016. Jenis penelitian ini adalah analitik observasional dengan rancangan cross-sectional. Sebanyak 199 rekam medis pasien maternal yang masuk dalam kriteri inklusi dianalisis menggunakan uji Mann-Whitney dan uji Chi-Square. Uji Fisher digunakan apabila syarat uji Chi-Square tidak terpenuhi. Karakteristik pasien maternal di salah satu rumah sakit swasta di Yogyakarta yaitu minggu kelahiran normal (93%), suplementasi kalsium tidak sesuai (79%), umur â¤30 tahun (61%), tingkat pendidikan strata satu (53%), pekerjaan pegawai swasta (40%), antenatal care â¥4 kali (98%) dan paritas 1 dan â¥4 kali (54%). Hasil penelitian ini mengungkapkan tidak terdapatnya hubungan antara umur, antenatal care, riwayat abortus dan paritas serta suplemen kalsium (p>0,05) terhadap kelahiran prematur pada pasien maternal di salah satu rumah sakit swasta di Yogyakarta.Kata kunci: Kelahiran prematur, maternal, suplementasi kalsium